2018
DOI: 10.1111/1753-0407.12650
|View full text |Cite
|
Sign up to set email alerts
|

Non‐high‐density lipoprotein cholesterol:  High‐density lipoprotein cholesterol ratio is an independent risk factor for diabetes mellitus: Results from a population‐based cohort study

Abstract: The non-HDL-C:  HDL-C ratio was found to be an independent risk factor for diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 12 publications
2
53
0
Order By: Relevance
“…For further research, we were excluded missing values of baseline TG (n = 5747) and HDL-C (n = 89,231) from the analysis cohort. And then TG/HDL-C was calculated as TG divided by HDL-C, we excluded outliers of TG/ HDL-C(<means minus three standard deviation (SD) or > means plus three SD) (n = 2068) [13]. The final analysis included 114,787 subjects (61,097 male and 53,690 female) for data analysis in our study.…”
Section: Data Source and Participantsmentioning
confidence: 99%
“…For further research, we were excluded missing values of baseline TG (n = 5747) and HDL-C (n = 89,231) from the analysis cohort. And then TG/HDL-C was calculated as TG divided by HDL-C, we excluded outliers of TG/ HDL-C(<means minus three standard deviation (SD) or > means plus three SD) (n = 2068) [13]. The final analysis included 114,787 subjects (61,097 male and 53,690 female) for data analysis in our study.…”
Section: Data Source and Participantsmentioning
confidence: 99%
“…besides being a substitute of IR, is associated with susceptibility of β-cells to glucotoxicity and lipotoxicity. Evidence suggested that elevated glucose levels can induced reactive oxygen species generation on islet β-cells, which in turn cause oxidative stress and β-cells dysfunction, and then lead to IR and T2DM [33][34][35]. Other studies revealed that long-term high free fatty acid content was related to prolonged exposure of TG in pancreatic islets, which may impair pancreatic β-cell function [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…The exploration of subgroup analysis and interaction was crucial for clinical research, which could better understand the true relationship between independent variables and dependent variables [20].…”
Section: Discussionmentioning
confidence: 99%
“…According to the recommendation of the STROBE statement[20], besides the unadjusted model, the results for mildly adjusted model (model 1) and fully adjusted model (model 2) were presented: model 1, adjusting for gender, age and BMI; model 2, additionally adjusted for SBP, DBP,…”
mentioning
confidence: 99%